Risk factors of the rebleeding according to the patterns of nonvariceal upper gastrointestinal bleeding - Nam, Ji Hyung; Jeon, Tae Joo; Cho, Jae Hee; Kim, Jae Hak (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Despite of successful endoscopic hemostasis of nonvariceal upper gastrointestinal bleeding (NGIB), rebleeding rate has not decreased. The aim of this study was to identify risk factors for rebleeding after endoscopic hemostasis in patients with NGIB according to bleeding patterns. Materials and Methods: A retrospective analysis was performed on the consecutive patients with NGIB in whom successful primary endoscopic hemostasis had been achieved at three university hospitals in Korea. All patients underwent endoscopic treatment with hemoclips, epinephrine injection, argon-plasma coagulation, or its combinations within 12 h. Results: A total of 198 patients were studied. The male-to-female ratio was 3:1. Mean age was 60.7±14.9 years. Rebleeding occurred in 41 cases (20.7%). Median day of rebleeding after endoscopic therapy was 2.0 days. Overall mortality rate was 5.1%. Risk factors for rebleeding were inpatients [odds ratio (OR) 2.61, 95% confidence interval (CI): 1.05-6.46, p=0.038) and Forrest Ib (OR=2.73, 95% CI: 1.15-6.47, p=0.023) by multivariate regression analysis. Conclusion: Despite of successful emergent endoscopic therapy for NGIB, rebleeding occurred in 17.7% within a week. Endoscopic treatments should be more carefully performed for patients in hospitalization or patients with active oozing. Cite this article as: Nam JH, Jeon TJ, Cho JH, Kim JH. Risk factors of the rebleeding according to the patterns of nonvariceal upper gastrointestinal bleeding. Turk J Gastroenterol 2017; 28: 266-71.